Association between systemic immune-inflammation index and mortality in critically ill patients with chronic obstructive pulmonary disease: insights from the MIMIC-IV database - Giri, Mohan; Puri, Anju; Huang, Lan; Guo, Shuliang (Frontiers in Medicine, 2025)
BackgroundChronic Obstructive Pulmonary Disease (COPD) is a major cause of morbidity and mortality, particularly among critically ill patients. Despite the well-established role of inflammation in COPD pathogenesis, the prognostic significance of the systemic immune-inflammatory index (SII) in these patients remains unclear. This study aimed to investigate the relationship between SII and mortality risk in critically ill patients with COPD.MethodsThis retrospective observational cohort study utilized data from 3,291 COPD patients extracted from the Medical Information Mart for Intensive Care-IV (MIMIC-IV 2.2) database. The participants were divided into quartiles based on their SII values. The primary endpoint was in-hospital mortality. The primary endpoint was compared across the four quartiles using Kaplan–Meier analysis. The relationship between the SII and mortality was analyzed using Cox proportional hazards models. Subgroup analyses and interaction tests were conducted to assess the robustness of the findings.ResultsA total of 3,291 patients with COPD were included in the study. The in-hospital, 90-day, and 1-year mortality rates were 15.1, 27.9, and 39.4%, respectively. The results of the multivariate Cox regression analysis revealed that an elevated SII was significantly associated with in-hospital mortality (HR: 1.17; 95% CI: 1.07–1.27; p < 0.001), mortality at 90 days (HR: 1.26; 95% CI: 1.17–1.34; p < 0.001), and mortality at 1 year (HR: 1.19; 95% CI: 1.13–1.26; p < 0.001). Furthermore, patients in the higher quartiles of SII demonstrated an increased risk of in-hospital mortality, as well as mortality at 90 days and 1 year. The trend test across quartiles showed a statistically significant positive association between higher SII levels and increased mortality risk in all models. Stratified analysis and interaction tests demonstrated that the association between SII and in-hospital mortality remained stable.ConclusionOur study demonstrates that a high SII is independently associated with an increased risk of mortality in critically ill COPD patients. SII may serve as a risk stratification and prognostication tool in patients with COPD. Larger prospective studies are needed to validate these findings.